THE BATIH FAMILY AS A WEAPON: ANALYSIS OF THE JOLO CATHEDRAL BOMB, PHILIPPINES - Chaidar, Al; Sahrasad, Herdi; Tabrani, Dedy (Department of Anthropology, 2019)
This article explain aboutÂ terroristâ€™s bombing toward a Roman Catholic cathedral in Jolo, southern Philippines, Sunday 27 January 2019 morning. At least 22 people were reportedly killed tragically and nearly 50 others were injured. The suicide bombing of the husband and wife exploded during Sunday Mass in Jolo is the first bomb explosion was carried out by a woman from inside the church who smashed benches, smashed windows and left the body of the victim at the Catholic church located in Jolo. The first explosion occurred at Jolo Cathedral in Sulu Province. The second bomb exploded outside the church after the congregation left to save themselves. The second bomb was carried out by a man who was the husband of the first bomber. This JoloÂ suicide bombing mimics the suicide bombing of a family of 8-9 May 2018 in Surabaya and Sidoarjo. Nobody thought that the perpetrators came from one whole family. Officers revealed that the bombers in the three churches were the families of Mr. Dita Oepriyanto and Mrs. Puji Kuswati. These parents invited their four children to take action in three different churches. Their four children have a very young and young age. Yusuf Fadil's son (18), Firman Halim (16), daughter of Fadhila Sari (12), and Pamela Riskita (9). The familial terroist bombing in Jolo dan Surabaya is a reflection that our world today is 'a world full of the thrill of underground revenge, inexhaustible and never satisfied in an explosion'. The present is a age of anger